Temperature and scarification on seeds germination of copernicia prunifera (Mill) H.E. Moore (Arecaceae) - Pivetta, K. F L [UNESP] (2013)
Copernicia prunifera, known as carnauba, is native to Brazil and presents great potential to be used in gardens and cultivation in pot. Palms species, with relatively few exceptions, can only be propagated by seeds; even so, there are no reports in the literature about the germination of this palm seeds. Several species of the Arecaceae family present seed physical dormancy in varying degrees, demanding treatments to improve germination. The objective of this work was to study the effects of temperature and mechanical scarification on seed germination of C. prunifera. The experimental design was entirely randomized in a factorial arrangement 6 x 2 (six conditions of temperature with or without mechanical scarification) with 4 replications and 25 seeds each. In accordance with the treatment, lateral scarifications were made on the seeds until appearance of the endosperm. Seeds were sown in moist fine vermiculite. Germination (%) and germination rate (GR) were evaluated. Germination data were arcsine (x/100)1/2 transformed before analysis of variance and germination rate data were not transformed. The means of the resulting values were then compared by the Scott-Knott test at 1% confidence level. It was concluded that the biggest germination percentage were obtained at alternated temperature of 25-35°C (92%) and at constant temperature of 25°C (87%). Seeds germinated faster at alternated temperature of 25- 35°C. Germination percentage was similar for the scarified and non-scarified seeds; however, scarified seeds germinated faster.